Mental Health Impact of the COVID-19 Pandemic on Frontline Healthcare Workers at a Tertiary Care Hospital in Rawalpindi, Pakistan - Mansoor, Sawera; Azad, Nadia; Zubair, Usama Bin; Waqar, Tahreem; Butt, Anam; Ain, Qurat ul (Journal of Pakistan Psychiatric Society, 2020)
Objective: To explore the factors associated with the mental health impact of the COVID-19 pandemic on the front-line health care workers at a tertiary care hospital in Rawalpindi, Pakistan Study Design: Cross sectional research Place and duration of study: This study was conducted from 6th May to 6th June 2020 at Fauji Foundation Hospital, Rawalpindi. Subjects and Methods: Through purposive sampling, all frontline healthcare workers involved in the care of positive or high suspicion cases of COVID-19 at Triage clinics and Corona wards were recruited. Depression Anxiety and Stress Scale (DASS) and Impact of events scale-revised (IES-R) were administered; factors associated with significant mental health impact were analyzed using SPSS 20.0 Results: A total of 94 frontline healthcare workers were made part of the sample. Out of all, 18 (19.1%) reported significant depression while 32 (34%) had significant anxiety. Female gender and greater degree of contact with PCR positive COVID-19 cases were significantly related with higher depression and anxiety. Significant stress was reported by 33 (35.1%); there was a significant association of higher stress with being female, single, a nurse or paramedic and a greater degree of contact with PCR positive COVID-19 cases. 38 (40.4%) participants showed presence of significant trauma; healthcare workers at corona isolation unit or ICU were amongst the most affected. Conclusion: Depression, anxiety, stress and trauma were common among the front liners fighting the COVID-19 pandemic. Special attention should be paid to the mental health needs of this vulnerable population, particularly females and those having a greater contact with PCR positive cases in high-risk settings